2022
DOI: 10.3390/en15103516
|View full text |Cite
|
Sign up to set email alerts
|

Exergetic Analysis of DME Synthesis from CO2 and Renewable Hydrogen

Abstract: Carbon Capture and Utilization (CCU) is a viable solution to valorise the CO2 captured from industrial plants’ flue gas, thus avoiding emitting it and synthesizing products with high added value. On the other hand, using CO2 as a reactant in chemical processes is a challenging task, and a rigorous analysis of the performance is needed to evaluate the real impact of CCU technologies in terms of efficiency and environmental footprint. In this paper, the energetic performance of a DME and methanol synthesis proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…They found out that total CO 2 underground storage led to exergy destruction of 1.34 MJ per kilogram of avoided carbon emissions, versus 0.13 MJ/kg for 75% CO 2 storage and 25% conversion into DME. 140 To increase DME yield, Koybasi et al investigated alternative reactor designs for a mixed CO 2 /CO reactant, including a cascade reactor system and a microchannel reactor with reactive and cooling channels. 141 Their results showed that the DME yield was higher for the microchannel reactor, notably due to the continuous cooling of the reactor by the cooling channels distributed within the reactor structure.…”
Section: Methanol and Dimethyl Ether Productionmentioning
confidence: 99%
See 3 more Smart Citations
“…They found out that total CO 2 underground storage led to exergy destruction of 1.34 MJ per kilogram of avoided carbon emissions, versus 0.13 MJ/kg for 75% CO 2 storage and 25% conversion into DME. 140 To increase DME yield, Koybasi et al investigated alternative reactor designs for a mixed CO 2 /CO reactant, including a cascade reactor system and a microchannel reactor with reactive and cooling channels. 141 Their results showed that the DME yield was higher for the microchannel reactor, notably due to the continuous cooling of the reactor by the cooling channels distributed within the reactor structure.…”
Section: Methanol and Dimethyl Ether Productionmentioning
confidence: 99%
“…Most studies on DME production from CO 2 fail to reach 10% yield, a reality that still limits the industrial feasibility of this process. De Falco et al proceeded to an exergy analysis of the DME synthesis process and compared it to CO 2 underground storage to evaluate the usefulness of such an operation (exergy is the amount of work that can be done with a given amount of energy) . They found that DME synthesis resulted in higher exergy destruction (i.e., higher energy loss), but resulted in a higher exergy efficiency compared to underground storage of CO 2 .…”
Section: Thermochemical Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, aside from the extensive research that has been conducted on the appropriate materials for catalyzing the respective CO 2 hydrogenation reaction, various works have assessed PtX from a techno-economic or environmental viewpoint. In general, although an overall conclusion cannot be unequivocally reached due to the casespecific nature of any such study, promising results have been obtained for PtX implementation at a wide scale range and based on a variety of CO 2 hydrogenation products, such as methanol [212][213][214], DME [215][216][217], liquid hydrocarbons [218][219][220][221][222][223][224] or light olefins [225,226]. Additionally, a comparison of these routes has been made in the recent review by Dieterich et al [202] and in the work by Atsbha et al [220].…”
mentioning
confidence: 99%